2020
DOI: 10.1051/0004-6361/202038461
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the quiet Sun cell and network emission with ALMA

Abstract: Observations of the Sun at millimeter wavelengths with the Atacama Large Millimeter/submillimeter Array (ALMA) offer a unique opportunity to investigate the temperature structure of the solar chromosphere. In this article we expand our previous work on modeling the chromospheric temperature of the quiet Sun, by including measurements of the brightness temperature in the network and cell interiors, from high-resolution ALMA images at 3 mm (Band 3) and 1.26 mm (Band 6). We also examine the absolute calibration o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
(41 reference statements)
4
17
0
Order By: Relevance
“…This observation (also studied in Alissandrakis et al [93]) represents the most quiescent solar region among our sample. ALMA’s FOV (and its immediate vicinity) includes several small magnetic concentrations, which seem to form some relatively weak network and internetwork areas.…”
Section: Analysis and Resultssupporting
confidence: 69%
“…This observation (also studied in Alissandrakis et al [93]) represents the most quiescent solar region among our sample. ALMA’s FOV (and its immediate vicinity) includes several small magnetic concentrations, which seem to form some relatively weak network and internetwork areas.…”
Section: Analysis and Resultssupporting
confidence: 69%
“…The solar radius results (Table 1) indicated that the half-power method yield larger radius values when compared to the inflectionpoint method -the values derived from ALMA maps are about 1 larger, while the ones derived from SST maps are about 10 larger. Also, the inflection-point method radii are closer to the radius measurements reported in the literature (Selhorst et al 2019a;Alissandrakis et al 2020;Menezes et al 2021). Moreover, considering the uncertainties, the radii are in agreement with the SSC model radius predictions, R ssc and 𝑅 conv ssc , except R ssc at 100 GHz and 𝑅 conv ssc at 212 GHz.…”
Section: Radius Determinationsupporting
confidence: 86%
“…Finally, all snapshot images were combined with contemporaneous full-disk ALMA images in order to recover large spatial scales that are not available to the interferometer, and obtain absolute brightness temperature calibration. We note that the correction of the brightness temperature at the solar disk center deduced by Alissandrakis et al (2020) for ALMA Band 6 applies only to full disk images and not to the interferometric images, whose flux calibration is established via the ALMA Calibrator Device (see Shimojo et al 2017a for details).…”
Section: Data Reduction and Overall View Of The Observationsmentioning
confidence: 99%
“…Using observations of absorption lines formed at heights from about 130 to about 1000 km, Canfield and Musman (1973) found that the p-mode energy density decreases with height from 2 × 10 2 erg cm −3 at 130 km to to 4 × 10 −1 erg cm −3 at a height of 1000 km. Alissandrakis et al (2020) used full-disk ALMA images to detect the solar limb and derived an emission height of 2400±1700 km for Band 6, which is above the heights scanned by Canfield and Musman (1973). This implies that the decreasing trend in the p-mode energy density with height extends above 1000 km.…”
mentioning
confidence: 97%
See 1 more Smart Citation